Game Edukasi Belajar Mengaji Menggunakan Metode Linear Congruent Method (LCM) Berbasis Android - Lita Sari Muchlis; Gerry Ronaldo Septianus (Jurnal Informatika Universitas Pamulang, 2020)
Koran refers to the activity of reading the Qur'an. Koran is a skill that must be mastered by every Muslim and must be taught from an early age to children from the preschool age is the formation of the main character. But at this age still playing and when studying the Koran is still conventional with limited teaching methods. The method of learning for preschoolers requires interactive learning in the form of interactive audio visual education game. In the midst of a lot of research on educational learning games of the Koran, researchers focus on using the Linear Congruent Method (LCM). This linear congruent method model is used to randomize the quiz questions that will be presented. In developing each component of this educational learning learning game software using the Rapid Application Development (RAD) model. The results achieved from this study are in the form of teaching learning applications that are ready for use. This application can be used as the best solution to make it easier for preschool children to study Koran and data from distribution test results in graphical form showing system assessments with the percentage of satisfaction of this application using the Computer System Usability Questionnaire (CSUQ) to get a value with an average of 86.46% in. in the very decent category.